论新加坡中华总商会的国家认同（1906-1965）= National identity of the Singapore Chinese Chamber of Commerce (1906-1965) - 吴雨芳 Goh, Yu Fang (Nanyang Technological University, 2020)
本文是以新加坡中华总商会的国家认同为中心展开的研究。总商会在1906年成立至1965年新加坡独立前，频繁活动于新加坡和中国，反映出其国家认同。本研究发现，总商会的成立有中国清政府、新加坡华社和英殖民政府不同程度的参与，由此奠定其双重身份，之后的活动和国家认同也受到相应的影响。在成立至新加坡沦陷前这一时期（1906-1942），总商会在中国进行了政治、经济和社会方面的活动，同时在新加坡也有所行动，从而显示其中国认同和新加坡认同两种不同情况。不过，在二战后至新加坡独立前这一时期（1945-1965），新中两国时局有变，总商会活动情况发生变化，一方面中国相关活动减少，另一方面涉及新加坡政治、经济和社会的活动全面展开，表现了国家认同的转变。总之，在独立前的动荡时代，总商会做出选择并进行相应的活动，其国家认同最后呈现出此消彼长的局面。This paper focuses on the national identity of Singapore Chinese Chamber of Commerce. The chamber’s national identity was shown by its frequent activities in Singapore and China from 1906 when the chamber was established, to 1965 when Singapore gained independence. The paper explores the parties involved in the chamber‘s establishment, which were China’s Qing government, Singapore's Chinese community, and British colonial government. These three parties had different extent of involvement, eventually, led to the chamber’s dual role and also affected its future events and national identity. After the chamber’s establishment, before the Japanese occupation of Singapore in 1942, China identity and Singapore identity were observed as the chamber organised events related to China’s politics, economy and society while being active in Singapore. However, after World War II ended in 1945 and before Singapore’s independence, situations had changed in Singapore and China, causing an adjustment in the chamber’s activities. Events related to China decreased while events related to Singapore’s politics, economy and society were in full swing, and a change in the chamber’s national identity was observed. In conclusion, the chamber made choices and performed actions accordingly during the turbulent period before Singapore’s independence, presenting a rise and fall of its dual national identity.